PROBLEMS AND SOLUTIONS TO INCREASE PUBLICATION ACTIVITY AT UNIVERSITIES AND SCIENTIFIC CENTERS OF UZBEKISTAN - Pazilova, Nargiza; Rakhmatullaev, Marat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article analyses the publication activity in the Republic of Uzbekistan during the years of independence. A background has been given to the collection of funds for academic libraries until 1991, in the early 90s and over the past decades, where the dynamics of changes in the number of scientific publications in universities is traced. An analysis is given of the reasons for the decline in interest in scientific research, the publication of scientific papers in high-ranking journals, as well as trends in solving these problems in the country. The results of analytical studies of data from information systems Scopus and Web of Science are presented. The factors that most influence the quality of teaching and research are highlighted. The authors of the article expound their personal experience in conducting seminars, trainings, and master classes at universities in Uzbekistan. The article presents a training program for doctoral students, teachers and researchers on the use of world electronic information resources of leading publishers, as well as an analysis of their effectiveness. Information is also given on the reforms carried out in the country in recent years in the field of supporting libraries and scientific research, which have contributed to increasing publication activity.